Long-term neuropathic pain behaviors correlate with synaptic plasticity and limbic circuit alteration: a comparative observational study in mice. Issue 8 (3rd August 2022) - Guida, Francesca; Iannotta, Monica; Misso, Gabriella; Ricciardi, Flavia; Boccella, Serena; Tirino, Virginia; Falco, Michela; Desiderio, Vincenzo; Infantino, Rosmara; Pieretti, Gorizio; de Novellis, Vito; Papaccio, Gianpaolo; et al.
Abstract : Characterizing long-term neuropathic pain: behavioral deficits and brain circuit dysfunctions and gene regulation across prefrontal cortex and limbic regions. Abstract: Neuropathic pain has long-term consequences in affective and cognitive disturbances, suggesting the involvement of supraspinal mechanisms. In this study, we used the spared nerve injury (SNI) model to characterize the development of sensory and aversive components of neuropathic pain and to determine their electrophysiological impact across prefrontal cortex and limbic regions. Moreover, we evaluated the regulation of several genes involved in immune response and inflammation triggered by SNI. We showed that SNI led to sensorial hypersensitivity (cold and mechanical stimuli) and depressive-like behavior lasting 12 months after nerve injury. Of interest, changes in nonemotional cognitive tasks (novel object recognition and Y maze) showed in 1-month SNI mice were not evident normal in the 12-month SNI animals. In vivo electrophysiology revealed an impaired long-term potentiation at prefrontal cortex-nucleus accumbens core pathway in both the 1-month and 12-month SNI mice. On the other hand, a reduced neural activity was recorded in the lateral entorhinal cortex-dentate gyrus pathway in the 1-month SNI mice, but not in the 12-month SNI mice. Finally, we observed the upregulation of specific genes involved in immune response in the hippocampus of 1-month SNI mice, but not in the 12-month SNI mice, suggesting a neuroinflammatory response that may contribute to the SNI phenotype. These data suggest that distinct brain circuits may drive the psychiatric components of neuropathic pain and pave the way for better investigation of the long-term consequences of peripheral nerve injury for which most of the available drugs are to date unsatisfactory.